Business Architecture Design in Indonesia’s Property Development Industry - Maria Veronika; Erick Dazki; Eko Indrajit (TEPIAN, 2025)
In the highly complex Indonesian property development industry, companies require a robust framework to effectively integrate diverse business and technological elements. This study addresses this need by designing a comprehensive business architecture model utilizing an Enterprise Architecture approach and ArchiMate modeling language. The research began by employing Business Model Canvas (BMC) to identify and analyze four primary revenue streams for property development companies: property sales, leasing income, hospitality income, and revenue from the retail and entertainment sectors. For each of these streams, a detailed business architecture model was constructed using ArchiMate, meticulously mapping the intricate relationships between key components such as business actors, business processes, supporting applications, data, and underlying system technologies. The resulting four business architecture models visually articulate the value flows and critical interconnections within each revenue stream. These models provide valuable insights, demonstrating how property developers can strategically manage, optimize, and align their operations with overarching business objectives. This research makes a significant contribution to the understanding and application of Enterprise Architecture within the property industry. It showcases the potential of ArchiMate to create more structured, integrated, and strategically aligned business models. The findings are intended to serve as a practical reference for property development companies in Indonesia, guiding them in the design and management of their business models to enhance competitiveness and drive sustainable growth in a dynamic market.